(untitled) (KULT_online, 2012)
The volume Literarische Stadtutopien zwischen totalitärer Gewalt und Ästhetisierung (Literary Utopia of Cities between Totalitarian Violence and Aestheticization), edited by Barbara Ventarola in 2011, discusses in an introduction and thirteen articles new horizons concerning literary utopia of cities, mainly in French literature. This highly constructive volume focuses successfully on a re-conceptualization of utopia, a revision of the history of utopia and the development of new city concepts. The volume gives a broad overview of different types of utopia.